The Influence of Effective Leadership and Organizational Trust to Teacher’s Work Motivation and Organizational Commitment - Diah Pranitasari (Media Ekonomi dan Manajemen, 2020)
This study aims to determine how the influence of organizational leadership and organizational effectiveness on work motivation and organizational commitment of teachers. This research was conducted at a private high school in Rawamangun Village, Pulo Gadung Subdistrict, East Jakarta. In this study using a saturated sample technique that is the entire population used as a sample, namely 115 respondents. The Partial Least Square Structural Equation Modeling (PLS-SEM) method was chosen as a statistical analysis technique. The results showed that the effectiveness of leadership and organizational trust had a direct positive effect on work motivation. The effectiveness of organizational leadership and trust has a direct positive effect on organizational commitment. Leadership effectiveness has a direct positive effect on organizational trust and work motivation has a direct positive effect on organizational commitment. The output of this research is that it can provide input for the school in determining policies specifically in determining the position requirements or the recruitment of school principals so that it is expected to increase the confidence, work motivation and commitment of teachers in school organizations.